2007
DOI: 10.4097/kjae.2007.53.3.s7
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Lidocaine, Fentanyl, Nicardipine, and Esmolol on Hemodynamic and Bispectral Index Responses during Induction with Thiopental Sodium

Abstract: Background: The laryngoscopy and tracheal intubation may accompany with undesirable side effects such as hypertension, tachycardia, arrhythmia, and awareness. The aim of this study was to investigate whether the correlation between the hemodynamics and bispectral index (BIS) changes after tracheal intubation following the administration of various adjuvants to attenuate tracheal response exists or not. Methods: The patients were randomly assigned to one of five groups (control, lidocaine, fentanyl, nicardipine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
(36 reference statements)
1
3
0
Order By: Relevance
“…Also, a study was done in Korea (2007) showed that the heart rate was significantly lower in fentanyl group compared to lidocaine group at first, second and third minute after intubation (p > 0.05) [14]. Same results were reported in another study [15].…”
Section: Discussionsupporting
confidence: 53%
“…Also, a study was done in Korea (2007) showed that the heart rate was significantly lower in fentanyl group compared to lidocaine group at first, second and third minute after intubation (p > 0.05) [14]. Same results were reported in another study [15].…”
Section: Discussionsupporting
confidence: 53%
“…The observations are consistent with the findings of by Jiang Yong, et al [22] who reported that a single dose of esmolol 1mg/ Kg better attenuate diastolic blood pressure than 0.5 mg/kg given before intubation. Shin, et al [25] also noted a significant fall in mean diastolic blood pressure compared to baseline values at all the measurement times (Table 8).…”
Section: Diastolic Blood Pressurementioning
confidence: 73%
“…Journal of Anesthesia & Intensive Care Medicine systolic blood pressure than 0.5 mg/kg given before intubation. Shin H Y, et al [25] observed that there were significant differences in the mean arterial pressure between control group and other groups (Table 7).…”
mentioning
confidence: 89%
“…that compared the effects of lidocaine, fentanyl, Nicardipine and Esmolol, on the hemodynamic response during intubation and those studies showed that all the agents are effective in producing hemodynamic stability. 27 According to Levitt et al Esmolol and lidocaine have similar efficacies to attenuate moderate hemodynamic responses to intubation in patients with isolated head trauma. 28 Additionally, Malde and Sarode in a 2007 study compared lignocaine and fentanyl efficacy on hemodynamic stability and revealed that lignocaine and fentanyl both attenuated the rise in heart rate, however, fentanyl produced better results.…”
Section: Discussionmentioning
confidence: 99%